Adaptation portfolio – a multi-measure framework for future floods and droughts - Saritha Padiyedath Gopalan; Naota Hanasaki; Adisorn Champathong; Taikan Oki (npj Natural Hazards)
Abstract Adaptation is critically important for coping with climate change. However, quantitative studies on which adaptation measures should be taken to maintain the present water risk level in the context of climate change have been explored little, particularly at large basin scales. Here, we devised three adaptation portfolios composed of combinations of measures to alleviate floods and drought with explicit basin-wide modelling in the Chao Phraya River basin, Thailand. Two portfolios mitigated future water scarcity to the present level but failed to eliminate extreme floods. The remaining portfolio with basin-wide reforestation substantially reduced the number of future flooding days but enhanced the number of drought months to 3–6 months a year, resulting from increased evapotranspiration by 7–11%. Overall, future flood adaptation remains challenging even in highly regulated rivers. We also observed that adaptation effects differ substantially by sub-basins. It highlights the necessity of spatio-temporal detailed impact modelling, including multiple adaptation measures.